YouTube as a potential training resource for laparoscopic fundoplication - Frongia, Giovanni; Mehrabi, Arianeb; Fonouni, Hamidreza; Rennert, Helga; Golriz, Mohammad; Günther, Patrick (Journal of surgical education, 2016)
To analyze the surgical proficiency and educational quality of YouTube videos demonstrating laparoscopic fundoplication (LF). In this cross-sectional study, a search was performed on YouTube for videos demonstrating the LF procedure. The surgical and educational proficiency was evaluated using the objective component rating scale, the educational quality rating score, and total video quality score. Statistical significance was determined by analysis of variance, receiver operating characteristic curve, and odds ratio analysis. A total of 71 videos were included in the study; 28 (39.4%) videos were evaluated as good, 23 (32.4%) were moderate, and 20 (28.2%) were poor. Good-rated videos were significantly longer (good, 22.0 ± 5.2min; moderate, 7.8 ± 0.9min; poor, 8.5 ± 1.0min; p = 0.007) and video duration was predictive of good quality (AUC, 0.672 ± 0.067; 95% CI: 0.541-0.802; p = 0.015). For good quality, the cut-off video duration was 7:42 minute. This cut-off value had a sensitivity of 67.9%, a specificity of 60.5%, and an odds ratio of 3.23 (95% CI: 1.19-8.79; p = 0.022) in predicting good quality. Videos uploaded from industrial sources and with a higher views/days online ratio had a higher objective component rating scale and total video quality score. In contrast, the likes/dislikes ratio was not predictive of video quality. Many videos showing the LF procedure have been uploaded to YouTube with varying degrees of quality. A process for filtering LF videos with high surgical and educational quality is feasible by evaluating the video duration, uploading source, and the views/days online ratio. However, alternative videos platforms aimed at professionals should also be considered for educational purposes.